Therapeutic failure with itraconazole in sporotrichosis due to bariatric surgery, - Larissa Crestani; Bruno de Castro e Souza; Priscila Kakizaki; Neusa Yuriko Sakai Valente (Sociedade Brasileira de Dermatologia, 2020)
Abstract Sporotrichosis is a deep mycosis of subacute or chronic evolution, caused by the dimorphic fungus of the genus Sporothrix. The treatment is carried out with antifungal orally or intravenously. Therapeutic success can be affected by several factors, such as altered gastrointestinal physiology by surgery. More and more patients are submitted to bariatric surgeries and the literature for the alterations of the absorption of medications in this context is very scarce. We intend to contribute to a better understanding with this case report of cutaneous-lymphatic sporotrichosis in a patient after bariatric surgery without response to itraconazole treatment, even at high doses.